Interventional strategies for ischemic stroke based on the modulation of the gut microbiota - Wang, Jing; Liu, Xiaofeng; Li, Qun (Frontiers in Neuroscience, 2023)
The microbiota-gut-brain axis connects the brain and the gut in a bidirectional manner. The organism's homeostasis is disrupted during an ischemic stroke (IS). Cerebral ischemia affects the intestinal flora and microbiota metabolites. Microbiome dysbiosis, on the other hand, exacerbates the severity of IS outcomes by inducing systemic inflammation. Some studies have recently provided novel insights into the pathogenesis, efficacy, prognosis, and treatment-related adverse events of the gut microbiome in IS. In this review, we discussed the view that the gut microbiome is of clinical value in personalized therapeutic regimens for IS. Based on recent non-clinical and clinical studies on stroke, we discussed new therapeutic strategies that might be developed by modulating gut bacterial flora. These strategies include dietary intervention, fecal microbiota transplantation, probiotics, antibiotics, traditional Chinese medication, and gut-derived stem cell transplantation. Although the gut microbiota-targeted intervention is optimistic, some issues need to be addressed before clinical translation. These issues include a deeper understanding of the potential underlying mechanisms, conducting larger longitudinal cohort studies on the gut microbiome and host responses with multiple layers of data, developing standardized protocols for conducting and reporting clinical analyses, and performing a clinical assessment of multiple large-scale IS cohorts. In this review, we presented certain opportunities and challenges that might be considered for developing effective strategies by manipulating the gut microbiome to improve the treatment and prevention of ischemic stroke.